Isolation of Amylolytic Strains of Thermoactinomyces vulgaris and Production of Thermophilic Actinomycete Amylases - Kuo, M. J. (1966)
Kuo, M. J. (Iowa State University, Ames), and P. A. Hartman. Isolation of amylolytic strains of Thermoactinomyces vulgaris and production of thermophilic actinomycete amylases. J. Bacteriol. 92:723–726. 1966.—Of 759 isolates obtained from dung, compost, and soil samples, a culture of Thermoactinomyces vulgaris (strain 5) was selected for further study on the basis of quantities of amylase produced in synthetic and nonsynthetic media, rapid growth and sporulation, culture stability upon prolonged storage at 5 C, and growth temperature range. Inoculum preparation, temperature optimum for amylase formation, and the effects of various kinds and levels of carbon and nitrogen sources on amylase production were studied with T. vulgaris strain 5. An optimal procedure for production of T. vulgaris amylases is proposed.